Characteristics associated with denial of problem drinking among two generations of individuals with alcohol use disorders. (1st December 2020) - Schuckit, Marc A.; Clarke, Dennis F.; Smith, Tom L.; Mendoza, Lee Anne
Highlights: Data are from two generations in a single study. There is little research regarding denial of alcohol problems by individuals with Alcohol Use Disorders (AUDs). A majority of subjects of first (67 %) and second generations (82 %) were identified as deniers of problems. Predictors of denial were generally different across generations. Asking more specific questions about alcohol problems is likely to improve the identification of individuals with AUDs. Abstract: Background: Denial of an overarching alcohol problem despite endorsement of specific alcohol-related difficulties may be central to development and continuation of alcohol use disorders (AUDs). However, there is limited information about which characteristics of drinkers and which drinking problems relate most closely to that denial. Methods: Using data from two generations of the San Diego Prospective Study (SDPS), we compared AUD subjects who considered themselves non-problematic drinkers (Group 1) with those with AUDs who acknowledged a general alcohol problem (Group 2). Comparisons included demography, alcohol-related patterns and problems, drug use, as well as impulsivity and sensation seeking. Variables were first evaluated as univariate characteristics after which significant group differences were entered in logistic regression analyses. Results: Sixty-seven percent of 94 AUD probands and 82 % of 176 AUD offspring reported themselves as light or moderate social drinkers despite averages of up to 12 maximum drinks per occasion and four DSM problems. Regression analyses indicated deniers evidenced less intense alcohol and drug-related problems and identified DSM-IV criterion items that they were most likely to deny. Conclusions: A large majority of two generations of SDPS participants whose interviews indicated a current AUD did not characterize themselves as problem drinkers. Despite drinking amounts that far exceeded healthy limits and admitting to important life problems with alcohol, these individuals give misleading answers regarding their condition when asked general questions about drinking by health care deliverers. The authors offer suggestions regarding how to identify those drinkers in need of advice regarding dangers of their behaviors.